When Following the Rules Feels Wrong. Issue 1 (25th February 2021) - Tate, Tyler
Abstract: The Covid‐19 pandemic has created a clinical environment in which health care practitioners are experiencing moral distress in numerous and novel ways. In this narrative reflection, a pediatric palliative care physician explores how his hospital's strict visitation policy set the stage for moral distress when, in the early months of the pandemic, it prevented two parents from being together at the bedside of their dying child .